Endogenous Political Institutions - Aghion, P.; Alesina, A.; Trebbi, F. (Quarterly Journal of Economics, 2004)
A fundamental aspect of institutional design is how much society chooses to delegate unchecked power to its leaders. If, once elected, a leader cannot be restrained, society runs the risk of a tyranny of the majority, if not the tyranny of a dictator. If a leader faces too many ex post checks and balances, legislative action is too often blocked. As our critical constitutional choice, we focus upon the size of the minority needed to block legislation, or conversely the size of the (super)majority needed to govern. We analyze both “optimal” constitutional design and “positive” aspects of this process. We derive several empirical implications which we then discuss.